Improving Students' Learning Understanding of Free Socialization Materials through the Use of Visual Media in Class VIII G SMP Negeri 8 Banjarbaru - Zaini, Akhmad; Rakhman, Arie; Putra, Trinaldi Andika (Empiricism Journal, 2026)
This study was conducted in response to the limited understanding of students in Class VIII G at SMP Negeri 8 Banjarbaru regarding free association material, which was influenced by learning activities that were still dominated by the teacher and the limited use of engaging instructional media. The purpose of this research was to improve students’ learning comprehension through the application of visual media in the learning process. The study employed a Classroom Action Research (CAR) design implemented in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The subjects of the study were all 26 students of Class VIII G at SMP Negeri 8 Banjarbaru, consisting of 13 boys and 13 girls. Data collection instruments included observation sheets for student and teacher activities, learning outcome tests, and documentation. The test instruments were validated through expert judgment involving one PJOK teacher and one university lecturer, who assessed the instruments based on content relevance, clarity, and suitability with the learning objectives. Observation reliability was maintained through collaborative observation and discussion between the researcher and the observer to ensure consistency in recording classroom activities. Data analysis used descriptive comparative techniques by comparing students’ learning outcomes in the pre-cycle, cycle I, and cycle II stages. The findings showed a continuous improvement in student achievement, with the average score increasing from 72 in the pre-cycle to 82 in cycle I and 94 in cycle II. In addition, the number of students who achieved learning mastery also increased, where 24 students achieved mastery and 2 students had not yet reached the minimum mastery criterion in cycle II. These findings indicate that the implementation of visual media was effective in improving students’ understanding of free association material.